у=х^2-10 у=17-6х
х^2-10=17-6х
х^2+6x-27=0
D=36-4*(-27)=36+108=144
x1=(-6+12)/2=6/2=3 y1=3^2-10=9-10=-1
x2=(-6-12)/2=-18/2=-9 y2=(-9)^2-10=81-10=71
(3; -1) (-9;71)
1,(18)=1+0,(18)
0,(18)=x
18,(18)=100x
18+0,(18)=100x
18+x=100x
18=99x
x=18/99
x=2/11
0,(18)=2/11
1,(18)=1+0,(18) =1+2/11=13/11
2,(27)=7+0,(27)
0,(27)=x
27,(27)=100x
27+0,(27)=100x
27+x=100x
27=99x
x=27/99
x=3/11
0,(27)=3/11
1,(27)=1+0,(27) =1+3/11=14/11
0,(13)=x
13,(13)=100x
13+0,(13)=100x
13+x=100x
13=99x
x=13/99
0,(13)=13/99
2,(23)=7+0,(23)
0,(23)=x
23,(23)=100x
23+0,(23)=100x
23+x=100x
23=99x
x=23/99
x=23/99
0,(23)=23/99
2,(23)=2+0,(23) =2+23/99
У меня получилось: т.*(3;-1)
Вот рисунок: http://ifotki.info/10/00fd70deae83233827aa8e9a3d22dac55c7007115174198.jpg.html